Adolescent Needs Satisfaction and Frustration in Malaysia: A Cross-Cultural Consideration by Translation, Adaptation and Validation Procedure - Nor Azhar, Nurul Fathihah; Jusoh, Ahmad Jazimin; Handrianto, Ciptro (International Journal of Education, Information Technology, and Others, 2024)
The humans` psychological needs can lead to frustration or satisfaction. Satisfaction with regard to basic psychological needs is characterized as an energetic situation that causes a rise in confidence as well as a healthy motivational orientation promoting wellness. The aims of this study were to adapt the Basic Psychological Need Satisfaction and Frustration Scale (BPNSFS) for use in Malaysia and to indicate how levels of need satisfaction and frustration are related to the daily life of students in the classroom. The three core psychological demands of competence, autonomy, and relatedness are taken into account in the scale's measurement of satisfaction and frustration. The researchers relied on Brislin's (1970) outline of the back-translation method's basic framework to carry out the process of translating this instrument. To carry out the translation process, a total of eight qualified linguists who are experts in the language field were utilized. Other than that, the researcher employed the external critic approach to evaluate the content validity and linguistics. In general, expert assessors accepted the BPNSNF instrument items. It can be concluded the current research offers researchers a tool to evaluate students' basic psychological need satisfaction and frustration among adolescents.